Changing urban landscapes: the case of Feirinha in Araguaína (TO, Brazil): um estudo de caso da Feirinha em Araguaína (TO) (Terr@ Plural, 2022)
The text presents the problem of the rupture in the landscape and itseffects on the sense of belonging of the de-allocated subjects. This qualitative researchwas built through bibliographic review and interviews with traders of the formerAraguaína fair. The main understanding is that the landscape of the fair dictated afreezing of the first years of the formation of the urban space of Araguaína and, withthe growth of the city, this landscape became no longer accepted in the central area.With the new fair, there was a transformation from the “place of subversion” to the conceived place of “popular fair”. The transformations in the landscape provoked duality in the meanings of the landscape for the traders and for the city’s population, of acceptance and exclusion from the space.
Keywords: Urban-cultural landscape, Transformations, Fair.